Wages and living conditions of stevedores in Tacloban City. - Basilan, Rebelander; Bayquin, Eloisa B. (Rebelander Basilan [and] Eloisa B. Bayquin, 2010)
This study aimed to describe the wages and living conditions of stevedores in Tacloban City. Specifically, it inquired into the demographic characteristics of the stevedores, their living conditions vis-a-vis the wage they receive, the kind of compensation or wage system imposed on them, and the factors that led them to work as stevedores. Thirty percent (30%), which is equivalent to 50 respondents, of the total population of stevedores of the Leyte Integrated Port Services, Inc. (LIPSI), the sole stevedoring company in Tacloban City, were selected using purposive sampling to serve as respondents of the study. The study found out that stevedores in Tacloban City are mostly young (28 to 33 years old), married, have low educational attainment, and have relatively large household sizes. The study also revealed that they live below the international poverty line and thus have poor living conditions, receiving the minimum daily wage rate of (P238) that is not enough to meet their families' basic economic needs, especially their need for shelter. The low wage rate is also compounded by the irregularity of their working days. They work on a rotational basis so that there are days when they do not have work, especially when ships are few, thus earning no wage. As prescribed by law, however, stevedores receive the legally mandated benefits and bonuses. This study also found out that the primary reason that led respondents to work as stevedores is to finance their daily living.